Synthesis and Application of Nano- and Microdispersed Systems - Kuznetsov, Denis; Burmistrov, Igor; Karunakaran, Gopalu; Muratov, Dmitry S.; Andrey, Yudin (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nano- and microdispersed systems can be defined as dispersions of the nano- and microparticles (droplets, bubbles) of one material within a continuous phase of another material (gas, liquid, solid). Such systems are very widespread in nature. The most common examples include soils, aerosols, minerals, and various natural colloids. Nano- and microdispersed systems are also the subject of active research and represent a techno-economic sector with full expansion in many application domains. Nano- and microdispersed systems have gained prominence in technological advancements due to their diverse physicochemical and mechanical properties, including wettability, dispersion stability, electrical and thermal conductivity, and catalytic activity, resulting in enhanced performance over their counterparts with a particle size above 1 µm. Such systems are of interest to various research areas, including the development of new polymers and ceramic composites, sensors, biomaterials, energy conversion devices, wastewater treatment strategies, and many other applications. The present Special Issue of Processes will include recent enhancements in the synthesis and application of various types of nano- and microdispersed systems and will help to expand scientific cooperation in this important field of research.